Implementation of precedence walking assistance mechanism in exoskeleton with only vertical ground reaction forces. Issue 3 (1st January 2014) - Cha, D.; Oh, S.; Kim, K.I.; Kim, K.‐S.; Kim, S.
Abstract : A more rapid detection method for step initiation is an important challenge for muscle force reduction in lower limb exoskeletons. Many studies have attempted to detect step initiation faster via either the precedence walking assistance mechanism or the shadow walking assistance mechanism. Although the precedence walking assistance mechanism is the fastest for the detection of step initiation, this mechanism has limitations while using biosignals. As a result, many studies have attempted to detect step initiation with the shadow walking assistance mechanism as soon as possible. A precedence walking assistance mechanism has been implemented for step initiation in the Unmanned Technology Research Centre Exoskeleton (UTRCEXO) based on gait analysis without using any biosignals. Success was achieved in reducing the muscle force of the operator.